Efficient Coded-Block Delivery and Caching in Information-Centric Networking - Yan Liu; Jun Cai; Huimin Zhao; Shunzheng Yu; JianLiang Ruan; Hua Lu (Discrete Dynamics in Nature and Society)
Information-centric networking (ICN) provides request aggregation and caching strategies that can improve network performance by reducing content server loads and network traffic. Incorporating network coding into ICN can offer several benefits, but a consumer may receive the same coded block from multiple content routers since the coded block may be cached by any of the content routers on its forwarding path. In this paper, we introduce a request-specific coded-block scheme to avoid linear dependency of blocks that are utilizing in-network caching. Additionally, a non-cooperative coded caching and replacement strategy is designed to guarantee that the cached blocks can be reused. Our experimental results show that the proposed scheme has superior performance to conventional CCN and two network coding-based ICN schemes.